CONSTRUCTIVE ANALYSIS OF CARGO PLATFORMS OF DUMP TRUCKS - A.A.Gaffarov; L.N.Atakulov (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation; This article analyzes the structure of the cargo platforms of dump trucks used in the mining industry, their structural features and efficiency. It also discusses the structural design of various cargo platforms and their impact on the cargo transportation process.